Altered circulating microRNA profiles after endurance training: an ultramarathon runner cohort study. (14th October 2021) - Marszalek, M; Simon, J E; Fitas, A; Czajka, P; Eyileten, C; Wicik, Z; De Rosa, S; Postula, M; Malek, L; ,
Abstract: Background and aim: Characterized by prolonged, highly dynamic exercise that is low-to-high power in nature, endurance training has proven beneficial in cardiovascular disease prevention. Several miRNAs have been reported to be regulated in response to exercise in healthy humans. Our aim was to determine the miRNA expression changes before and after an ultramarathon run in elite runners [1]. Method: We performed bioinformatic analyses - tissue-specific/CV process-specific. Each bioinformatic analysis included 55 miRNAs (figure 1). The multiMiR 1.4 R package was used to identify the targets of miRNAs while a screening of the gene ontology terms for the presence of keywords with the biomaRt interface was used to identify genes associated with angiogenesis, cardiac muscle function, muscle hypertrophy, coagulation, inflammation, and fibrosis. Cardiac tissue-specific targets were identified in Tissue 2.0 database using expression confidence score >2. Gene-gene interaction data were retrieved from the STRING app for Cytoscape. Enrichment analyses of biological processes and reactome and KEGG pathways were also conducted on the STRING app. miR-1-3p, miR-126, miR-223, miR-125a-5p, miR-106a, and miR-15a/b were chosen, based on bioinformatic analysis for qRT-PCR validation, among those related to inflammation, fibrosis and cardiac function [2]. Total RNA was extracted from plasma samples using the MirVana PARIS Kit (ABI, California, USA) and quality was assessed using fluorometric assay. qRT-PCR was performed using the TaqMan Advance (ABI, Foster City, California) protocol on a high throughput thermal cycler. The Wilcoxon test was used for paired comparison – before vs after ultramarathon running – and Spearman's Correlation was used for database analysis of miRNA expressions, p<0.05. Results: MiR-1-3p, miR-126, miR-223, miR-125a-5p, miR-106a, and miR-15a/b expressions were measured in 22 endurance athletes before and after an ultramarathon wherein athletes ran to completion (100 km) or exhaustion (52–91 km, median 74 km). We found that the expressions of miR-125a-5p, miR-126, miR-223 were significantly increased after the ultramarathon (p=0.018; p=0.001; p=0.014, respectively), whereas miR-15b was significantly decreased (p=0.028). No significant difference was observed for miR-1-3p and miR-15a, while miR-106a was not detectable in the circulating plasma (figure 2). Additionally, miR-1-3p expression post-run showed negative correlation with hsCRP levels post-run (r=−0.631, p=0.005). miR-125a-5p expression post-run showed negative correlation with max lactate levels during run (r=−0.759, p=0.004). Conclusion: Extreme physical activity, as exemplified by an ultramarathon, may have an impact on the expression alterations of miRNAs associated with inflammation, fibrosis, and cardiac muscle function. Further studies will clarify the long-term impact of these observations. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Medical University of Warsaw